Virtual Reality Triage Training Can Provide Comparable Simulation Efficacy for Paramedicine Students Compared to Live Simulation-Based Scenarios. (3rd July 2020) - Mills, Brennen; Dykstra, Peggy; Hansen, Sara; Miles, Alecka; Rankin, Tim; Hopper, Luke; Brook, Luke; Bartlett, Danielle
Abstract: Background: Mass-casualty incidents (MCIs) are catastrophic. Whether they arise from natural or man-made disasters, the nature of such incidents and the multiple casualties involved can rapidly overwhelm response personnel. Mass-casualty triage training is traditionally taught via either didactic lectures or table top exercises. This training fails to provide an opportunity for practical application or experiential learning in immersive conditions. Further, large-scale simulations are heavily resource-intensive, logistically challenging, require the coordination and time of multiple personnel, and are costly to replicate. This study compared the simulation efficacy of a bespoke virtual-reality (VR) MCI simulation with an equivalent live simulation scenario designed for undergraduate paramedicine students. Methods: Both simulations involved ten injured patients resulting from a police car chase and shooting. Twenty-nine second-year paramedicine students completed the live and VR simulation in a random order. The training efficacy of the VR and live simulation was evaluated with respect to student immersion and task-difficulty, clinical decision-making (i.e. triage card allocation accuracy and timeliness), learning satisfaction, and cost of delivery. Results: While perceived physical demand was higher in the live simulation compared to VR ( p  < 0.001), no differences were observed across mental demand, temporal demand, performance, effort or frustration domains. No differences were found for participant satisfaction across the two platforms. No differences were observed in the number of triage cards correctly allocated to patients in each platform. However, participants were able to allocate cards far quicker in VR ( p  < .001). Cost of running the VR came to AUD $712.04 (staff time), compared to the live simulations which came to AUD $9, 413.71 (staff time, moulage, actors, director, prop vehicle), approximately 13 times more expensive. Conclusion: The VR simulation provided near identical simulation efficacy for paramedicine students compared to the live simulation. VR MCI training resources represent an exciting new direction for authentic and cost-effective education and training for medical professionals.